Analisis Pemenuhan layanan Kesehatan pada Pengrajin Batik melalui Pos Upaya Kesehatan Kerja - Agus Warseno; Suryo Ediyono (Jurnal Indonesia Sehat, 2022)
Background: One of the activities of the informal economy is the Batik industry which concentrates on informal sector workers, namely those who are not registered and work contracts based on mutual trust between workers and job providers. There are many potential hazards in the workplace and result in losses for both the company, employees and the surrounding community. The growing development of the home batik industry can cause health problems for the batik artisans. Factors that can influence these health problems are due to the condition of the physical environment of the house, the batik production process that uses chemicals, and the waste it produces. The purpose of this study is to analyze and compare the literature related to the empowerment of informal workers. The Methode: A literature search was carried out in November 2022. The data used is secondary data obtained from the results of research conducted by previous researchers. This literature review search uses electronic databases, namely Google Scholar, Science Direct, Semantic Scholar by looking at the most recent year, and going back to an older year. The results show that batik artisans have a risk of being exposed to hot wax and steam from candles and stoves. In the batik printing process, the risks that can be experienced are hands and feet exposed to dyes, hands exposed to heat and blisters. Efforts to reduce the morbidity rate of work-related diseases, work-related diseases, and work accidents need to be carried out by fostering and inspecting workplaces and occupational health. Conclusion: One of the government programs in addressing occupational health problems, especially in the informal sector, is through Pos Upaya Kesehatan Kerja.